Social Networking Sites as a New Public Sphere: Facebook and its Potential to Facilitate Public Opinion as the Function of Public Discourse – A Case Study of the 2008 Obama Campaign - Smuts, Lize-Marie (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Political Science))--University of Stellenbosch, 2010.